Theological education in contemporary Africa - LeMarquand, Grant; Galgalo, Joseph D. (Zapf Chancery, 2004)
Part One addresses ëTheological Foundations.í The five essays in this section deal with the Bible, Theology and Ecumenism. The subjects of theological methods, contextual hermeneutics, and appropriate curriculum are given special attention. Of course even foundational issues cannot be discussed in a vacuum and so each of the essays addresses these foundational subjects in the light of African realities. Part Two deals with ëContemporary Issues.í It is particularly in this section that the traditional themes in African theology have been somewhat displaced by concerns which are today very press